RISK FACTORS AMONG HIV POSITIVE/AIDS PATIENTS: A PROSPECTIVE STUDY AT A TERTIARY CARE REFERRAL CENTRE - Ahmed, Rabia; Yusuf, Noshin Wasim; Javeid, Iqbal; Arif, Mizna; Haider, Sajjad (Journal of Ayub Medical College Abbottabad, 2012)
Background: HIV/AIDS is a global problem, South Asia and Africa bearing the maximum burden. The incidence is reported to be rising in Pakistan. It is important to document the prevalence of various risk factors in our population so that appropriate measures could be taken for preventing emergence of new cases. Objectives were to identify the possible etiological factors/high risk behaviour in cases diagnosed as HIV/AIDS presenting at a tertiary care referral centre. Methods: Prospective observational case series carried out over a one year period at HIV/AIDS referral centre at Allama Iqbal Medical College Lahore. Five hundred patients were included who were positive for HIV on screening devices and then confirmed by ELISA. All these patients were referrals from Punjab AIDS control programme (PACP). A detailed history was taken on a pre-designed Performa specially targeted to identify the known risk factors for HIV infection. Results: Five hundred HIV positive subjects diagnosed by screening device and confirmed on ELISA were included in the present study. Three hundred and fourteen (63%) were males and 186 (37%) were females. Mean age was 35±12 years. Most prevalent risk factor among these patients was sexual transmission followed by intravenous drug abuse, injections from substandard health facilities, and transmission from infected spouse. Conclusion: HIV/AIDS is a preventable disease if the risk factors are avoided. Community awareness for unsafe homo and heterosexual practices and discouraging visits to non qualified health practitioners should be the top priority by PACP apart from controlling the IDUs menace. Keywords: HIV, AIDS, Pakistan, Punjab, STD, epidemic, commercial sex worker, quackery, IDUs